Fostering Inclusion in Digital Marketplace: Vistas into the Online Shopping Experiences of Consumers with Visual Impairment in India - Greeshma Benny Thadikaran; Sandeep Kumar Singh (Organizations and Markets in Emerging Economies)
Online shopping has become increasingly prevalent in recent years, overshadowing traditional brick-and-mortar shopping. Research has tried to understand the online shopping experiences of various consumers. However, the online shopping experiences of consumers with visual impairment (CWV) gained less attention. This study captures the online shopping experiences of CWV by employing a phenomenological qualitative approach. Data was collected from CWV through semi-structured interviews. The sample size of this study was fifteen, and data was analyzed using NVivo14. The findings indicate a growing preference for online shopping among the CWV. The results explore the accessibility-related issues encountered by CWV and strategies employed to overcome them. Additionally, the paper underscores the benefits of independence and the impact of online shopping on the personal growth and well-being of CWV. The study provides insights to marketers to foster inclusion in the digital marketplace. This study helps marketers and other stakeholders to understand the online shopping experiences of CWV and ensures consumer well-being and inclusion.